Japan Decides 2012
XXII, 257 p.
Keywords: The 2012 election in Japan ejected the governing DPJ and returned the LDP overwhelmingly to power while brand new parties pulled in millions of voters. This book explains what happened, why it happened and what it means. International experts analyze the election results, parties strategies, gender issues, policy implications and more.